O pensador e o filósofo - A experiência (auto)biográfica da filosofia na filosofia e na literatura - Marcos Daniel Camolezi (Revista Criação & Crítica, 2010)
This article aims to discuss the possibilities of an (auto)biographical account of a philosophical experience. Through the discussion of some issues such as the subject-object relation, the distinction between phenomenon and thing-in-itself, the conditions of memory and some of language’s limitations, we engage, first of all, in a philosophical discussion about the knowledge of the human experience. Bergsonism is the organic basis for this discussion, from which, secondly, literature is conceived as a horizon of expression of experience and time. However, this does not mean that we will engage in a simple text analysis. What we want is to discuss the capacity of (auto)biographical accounts to handle such a complex experience as the philosophical one. As a memory image and as language, the account is beneath — or beyond — the experience itself, thus it is a witness of the distance between the thinker and his own interior dynamics.